Hepatitis B Virus Infection and Anti-HBc (Total) Positivity in CKD Patients before Dialysis (Journal of Enam Medical College, 2016)
Background: CKD patients are associated with HBV infection both as a cause and complication of treatment. CKD patients before starting dialysis therapy are considered as a high risk group because of impaired immune response compared with healthy individuals and also other risk factors related with treatment and management. Only HBsAg marker does not always follow the presence or absence of HBV infection. Anti-HBc (total) alone positivity indicates previous exposure to HBV infection, window period and even after reactivation of resolved HBV infection. In some cases only anti-HBc positivity is interpreted as possible chronic low dose HBV infection (chronic carriage). Predialytic CKD patients were tested with three serological markers [HBsAg, anti-HBc (total) and anti-HBs] for screening HBV infection. Proper diagnosis before dialysis and knowing the infection status would help both the patient and doctor to choose proper treatment approach.Objective: This cross-sectional study was done in the CKD patients before starting dialysis therapy to find out the HBV infection and to evaluate the infection by minimal serological markers as for screening.Materials and Methods: A total of 211 patients with chronic kidney disease stage five (CKD-V) before starting dialysis therapy were included as subjects of this cross-sectional study. Among the CKD patients HBsAg was tested to see the prevalence. Other serological markers, i.e., anti-HBc (total) and anti-HBs were tested in combination with HBsAg in 89 randomly selected patients among the subjects. The patients were also tested for anti-HCV to assess co-infection. After collecting all the data of different test results analyses were done by SPSS version 15.0.Results: Among total study population 10 (4.7%) patients were found HBsAg positive. No patient was found positive for both HBsAg and anti-HCV. Among the 89 CKD patients only 2 (2.2%) patients were HBsAg positive, and only one patient (0.9%) was found positive for both anti-HBc and anti-HCV. Of them, a total of 22 (24.7%) patients were anti-HBs positive, and 35 (39.3%) patients were anti-HBc (total) positive. Of the three markers anti-HBc (total) alone positivity were in 20 (22.5%) patients.Conclusion: Data indicate a large proportion of HBV infected patients were underdiagnosed by usual screening method by HBsAg in our country. The finding of anti-HBc (total) alone cannot be clearly interpreted in terms of patient prognosis or infectivity. Patients are simply regarded as potentially infectious. Due to this uncertainty, different countries employ different procedures when faced anti-HBc alone findings. In some countries including ours the test is not performed. Since a substantial number of CKD patients with HBV infection have this anti- HBc (total) positivity, standard screening procedures and precautions should be taken in blood donation, hemodialysis and for other invasive procedures to prevent transmission of infection.J Enam Med Col 2016; 6(3): 128-133